2022
DOI: 10.3390/ani12030294
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Soybean Products in Broiler Chicken Nutrition

Abstract: The study aimed to determine the overall effect of replacing soybean meal completely with soybean expeller cake or extruded full-fat soybean in feed rations for broiler chickens on their carcass composition and meat quality. The experiment involved one hundred and twenty Ross 308 broiler chickens randomly allocated to three equinumerous groups (SBM, SEC, EFS). Each group was divided into five subgroups—each consisting of eight birds of both sexes (1:1). From Day 1 to Day 21 of life the birds were fed with loos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
3
6
0
Order By: Relevance
“…Thus, indicated that addition of extruded pressed to diet of Ross308 broiler chicken did not have any adverse effect on growth performance and economic efficiency parameters. This is in agreement with that reported by (Janocha and Milczarek, 2022), who revealed that the best raising results were obtained when non-GM soybean expeller cake was completely substituted for GM soybean meals in broiler chicks.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, indicated that addition of extruded pressed to diet of Ross308 broiler chicken did not have any adverse effect on growth performance and economic efficiency parameters. This is in agreement with that reported by (Janocha and Milczarek, 2022), who revealed that the best raising results were obtained when non-GM soybean expeller cake was completely substituted for GM soybean meals in broiler chicks.…”
Section: Discussionsupporting
confidence: 93%
“…When soybeans are processed with the Insta-Pro Express TM extruder/press system, the resulting extruded-pressed soybean meal typically has a higher dry matter content and lower moisture content than soybean meal that has undergone conventional processing. In this study, the addition of extruded-pressed soybean meal to feed formulations of Ross308 broiler chickens allowed a significant increase in the BW, BWG and RGR of chicken with no effect on FCR and EBI ; these results were in agreement with that reported by (Janocha and Milczarek, 2022)and by (Meyer and Bobeck, 2021) who concluded that birds provided diets containing Extrudedpressed soybean meal gained more body weight overall and during each performance period than birds fed diets containing solvent-extracted SBM (SBM 46%).Also, This was consistent with the information provided by (Zhang et al, 1993), who mentioned that the body weight gain increased due to the presence of extruded-pressed SBM in the diet. Powell et al, (2011) did not observe any appreciable differences in the FCR.…”
Section: Discussionsupporting
confidence: 92%
“…Jahanian and Rasouli (2016) reported that carcass features were not affected, abdominal fat increased, and breast muscle yield was reduced when dietary soybean meal was replaced with 86% extruded soybean meal. In contrast, Janocha and Milczarek (2022) revealed a more significant proportion of the breast and leg muscles in broilers fed either soybean meal or soybean expeller cake when compared with birds fed extruded full-fat soybeans.…”
Section: Carcass Criteria and Internal Organsmentioning
confidence: 68%
“…There are countries in Europe that want to prohibit the use of genetically modified organisms (GMOs) in livestock nutrition altogether. An example is Poland, where this ban is planned to be introduced in 2024 [ 15 ].…”
Section: Introductionmentioning
confidence: 99%